2019
DOI: 10.1177/1758835919853196
|View full text |Cite
|
Sign up to set email alerts
|

A real-world analysis of second-line treatment options in pancreatic cancer: liposomal-irinotecan plus 5-fluorouracil and folinic acid

Abstract: Background: Nanoliposomal irinotecan (nal-IRI) plus 5-fluorouracil/leucovorin (5-FU/LV) is a novel treatment option for gemcitabine-pretreated metastatic pancreatic adenocarcinoma (PAC) patients, but real-world evidence is rare. Our aim was to determine the effectiveness and tolerability of this regimen in advanced PAC patients and to compare it with oxaliplatin plus fluoropyrimidines in the second-line setting after failure of gemcitabine. Methods: This is a retrospective single-center analysis of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 13 publications
13
73
2
Order By: Relevance
“…2.1 ). More recently, the effectiveness of this combination has been evaluated in several retrospective, observational (real-world evidence) studies from one [ 24 26 ] or more [ 27 – 32 ] institutions in Austria [ 24 ], Italy [ 30 ], South Korea [ 27 ], Taiwan [ 26 ] or the USA [ 25 , 28 , 29 , 31 , 32 ] (Sect. 2.2 ).…”
Section: Therapeutic Efficacy Of Liposomal Irinotecanmentioning
confidence: 99%
See 2 more Smart Citations
“…2.1 ). More recently, the effectiveness of this combination has been evaluated in several retrospective, observational (real-world evidence) studies from one [ 24 26 ] or more [ 27 – 32 ] institutions in Austria [ 24 ], Italy [ 30 ], South Korea [ 27 ], Taiwan [ 26 ] or the USA [ 25 , 28 , 29 , 31 , 32 ] (Sect. 2.2 ).…”
Section: Therapeutic Efficacy Of Liposomal Irinotecanmentioning
confidence: 99%
“…Real-world studies investigating nal-IRI + 5-FU/LV have enrolled individuals ( n = 44–296) with advanced PDAC (i.e. unresectable, locally advanced or metastatic disease) that had progressed following gemcitabine-based chemotherapy in the neoadjuvant or adjuvant setting, or in a prior line of treatment for advanced disease [ 24 – 32 ] (some results only available as an abstract and/or poster [ 28 , 30 , 32 ]). The median age of study populations was 60–69 years, 38–61% were males and, where specified, 54–100% of evaluable patients had ECOG PS 0–1, and 61–83% of evaluable patients had elevated CA 19-9 levels [ 24 27 , 30 – 32 ].…”
Section: Therapeutic Efficacy Of Liposomal Irinotecanmentioning
confidence: 99%
See 1 more Smart Citation
“…Applicability of CA 19-9 levels to determine therapeutic and prognostic responses in PDAC There have been numerous studies investigating the clinical relevance of CA 19-9 in pancreatic cancer, and to define its applicability in predicting either the responses or resistance to various treatments [28][29][30] . A summary of these investigations is given in Table 2.…”
Section: Human Studiesmentioning
confidence: 99%
“…A summary of these investigations is given in Table 2. Kieler et al [28] evaluated CA 19-9 levels in response to chemotherapy with nanoliposome irinotecan (nal-IRI) plus 5-fluorouracil/leucovorin (5-FU/LV) as a second-line treatment for PDAC and compared it with oxaliplatin plus fluoropyrimidines. The findings revealed that at the start of therapy, the median progression-free survival (PFS) was significantly longer in patients who received nal-IRI plus 5 FU/LV compared to the median PFS in patients treated with oxaliplatin plus fluoropyrimidines.…”
Section: Human Studiesmentioning
confidence: 99%